1992
DOI: 10.1042/bj2820545
|View full text |Cite
|
Sign up to set email alerts
|

Natural polyamines stimulate G-proteins

Abstract: The natural polyamines spermine and spermidine, the biosynthetic precursor putrescine and their analogues cadaverine and tyramine stimulate the GTPase activity of purified GTP-binding proteins (Go/Gi) from calf brain reconstituted into phospholipid vesicles. The order of potency was spermine greater than spermidine greater than putrescine = cadaverine greater than tyramine. The physiological relevance of this observation was assessed, showing the same order of potency of polyamines in the stimulation of perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 37 publications
3
52
0
1
Order By: Relevance
“…By contrast, the second model is supported by our results, which show that pretreatment of rabbit mucosa in the Ussing chamber with cadaverine protected the mucosa from the effect(s) of enterotoxins added after the cadaverine was washed from the tissue (see Results). Polyamines such as cadaverine are absorbed from the lumen by rabbit small intestine cells (33), and it has been proposed that intracellular polyamines might act as second messengers in the eukaryotic cell by modulation of extracellular signals transduced through G protein-coupled receptors (34). In this light, cadaverine could protect the cell by closing ion channels induced by bacterial toxins, altering intracellular signaling, or displacing toxin from cellular receptors.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the second model is supported by our results, which show that pretreatment of rabbit mucosa in the Ussing chamber with cadaverine protected the mucosa from the effect(s) of enterotoxins added after the cadaverine was washed from the tissue (see Results). Polyamines such as cadaverine are absorbed from the lumen by rabbit small intestine cells (33), and it has been proposed that intracellular polyamines might act as second messengers in the eukaryotic cell by modulation of extracellular signals transduced through G protein-coupled receptors (34). In this light, cadaverine could protect the cell by closing ion channels induced by bacterial toxins, altering intracellular signaling, or displacing toxin from cellular receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Basic secretagogues induce a rapid production of IP 3 , indicating concomitant PLC activation and histamine secretion (6,8,9,14,16). The present results confirm the participation of the PLC␤ family in this process, as could be predicted from its ability to be activated by heterotrimeric G proteins (35).…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylatoxin C3a, a fragment from the third component of complement, also belongs to the family of mast cell basic secretagogues (6), extending their interest in late immunological reactions. Other basic secretagogues include venom peptides such as mastoparan (4,7,8), polyamines such as spermine and compound 48/80 (9,10), and many cationic drugs currently being used therapeutically, with adverse effects related to mast cell activation (11).…”
mentioning
confidence: 99%
“…In particular, some reports have focused on the putative role of polyamines in the transduction of extracellular signals. For example, it has been suggested that G proteins may represent an important intracellular target for polyamines (Koenig et al, 1983;Bueb et al, 1992) and that these polycations influence the turnover of inositolphospholipids (Dureja- Munjal et al, 1992). On the other hand, much evidence has been provided regarding polyamine binding to cytosolic proteins.…”
Section: Dlscusslonmentioning
confidence: 99%